Fermentable carbohydrate intake and food avoidance behaviour in elderly patients with irritable bowel syndrome: A case report - Mohan Arumugam; Jane Jimson Simon; Ain Syahidah Ismail; Nur Amira Syahhirah Kamarulzaman; Zhiqin Wong; Shanthi Krishnasamy (Life Sciences, Medicine and Biomedicine, 2020)
Background: Fermentable carbohydrates or FODMAPs (Fermentable Oligo-, Di-, Monosaccharides, and Polyols) are short-chained, poorly absorbed carbohydrates which trigger gastrointestinal symptoms causing pain, bloating, distension, diarrhea, and constipation in Irritable Bowel Syndrome (IBS) patients. This debilitating condition has an impact on the quality of life of patients. In addition, due to lack of dietary intervention, it can result in food restriction to alleviate symptoms as patients avoid a wide variety of food and beverages. Objective: To compare FODMAP and nutrient intake, food avoidance behavior and quality of life in 2 long standing patients with IBS. Methods: Patients were selected on the basis of being diagnosed with IBS by a gastroenterologist. A 24-hour dietary recall with multiple pass method was used to assess intake. FODMAP intake was determined using published data. Symptom severity and quality of life was measured using a validated questionnaire. Meanwhile, food avoidance was assessed using a dietary trigger piloted questionnaire. Results: Two female Chinese patients with severe gastrointestinal symptoms were selected for this case series. Patient 1 was a 75-year-old female presenting with constipation-predominant IBS and patient 2 was a 61-year-old presenting with diarrhea-predominant IBS. Patient 1 had a higher energy intake: 2198 kcal, and FODMAP intake 10.6g/d, compared to patient 2 with an energy and FODMAP intake of 1800 kcal and 3.6g/d respectively. Both patients avoided a wide of range of food groups including cereals and grains, animal products, dairy and spicy foods. They also reported reduced scores for quality of life. Conclusion: Both patients had low intake of calcium as a result of food avoidance. This highlights the importance of appropriate and timely dietary intervention to this group of patients, to promote improved symptom management without compromising nutrient intake.